The dynamics of thefts and robberies in São Paulo’s Metro, Brazil - Ceccato, Vania (European journal on criminal policy and research, 2021)
The aim of this study is to assess the nature and space-temporal dynamics of property crimes (theft and robbery) in transport nodes, namely, metro stations and their immediate surrounding areas. The analysis is based on crime data over São Paulo’s metro system from 2010 to 2017. Drawing from environmental criminology theory, the methodology combines geographical information system (GIS) as well as statistical analysis using hypothesis testing and negative binomial regression models. Results show that thefts happen more often inside the station and robberies outside, with signs of possible interaction between these environments. Crime is often highly concentrated in a few inner city and end stations, but it varies depending on location and time. Future research and policy implications of the results add to the contribution of this current study.